Urolithins Are the Main Urinary Microbial-Derived Phenolic Metabolites Discriminating a Moderate Consumption of Nuts in Free-Living Subjects with Diagnosed Metabolic Syndrome - Tulipani, Sara; Urpi-Sarda, Mireia; Garcı́a-Villalba, Rocío; Rabassa, Montserrat; López-Uriarte, Patricia; Bulló, Mònica; Jáuregui, Olga; Tomás-Barberán, Francisco; Salas-Salvadó, Jordi; Espı́n, Juan Carlos; Andrés-Lacueva, Cristina (Journal of agricultural and food chemistry, 2012)
Walnuts (Juglans regia L.), hazelnuts (Corylus avellana L.), and almonds (Prunus dulcis Mill.) are rich sources of ellagitannins and proanthocyanidins. Gut microbiota plays a crucial role in modulating the bioavailability of these high molecular weight polyphenols. However, to date there are no studies evaluating the capacity to produce nut phenolic metabolites in subjects with metabolic syndrome (MetS), a pathology associated with an altered gut bacterial diversity. This study applied a LC-MS targeted approach to analyze the urinary excretion of nut phenolic metabolites in MetS subjects following 12 weeks of nut consumption, compared to sex- and age-matched individuals given a nut-free control diet. Metabolites were targeted in both hydrolyzed and nonhydrolyzed urine by LC-PDA-QqQ-MS/MS analysis, and identification of metabolites lacking available standards was confirmed by LC-ESI-ITD-FT-MS. Ellagitannin-derived urolithins A and B significantly increased after the nut-enriched-diet, urolithins C and D were also detected, and a complex combination of urolithin-conjugated forms was observed in nonhydrolyzed urine, confirming an extensive phase II metabolism after absorption. In contrast, no significant increases in proanthocyanidin microbial metabolites were observed in urine following nut consumption. Because the intestinal microbiota of the subjects in this study could catabolize ellagitannins into a wide range of urolithins, further research is strongly warranted on the in vivo potential of these microbial metabolites in reducing cardiometabolic risk.